2021
DOI: 10.3390/molecules26113133
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Enzyme Breaker for Fracturing Applications under Simulated Reservoir Conditions

Abstract: Fracturing fluids are being increasingly used for viscosity development and proppant transport during hydraulic fracturing operations. Furthermore, the breaker is an important additive in fracturing fluid to extensively degrade the polymer mass after fracturing operations, thereby maximizing fracture conductivity and minimizing residual damaging materials. In this study, the efficacy of different enzyme breakers was examined in alkaline and medium-temperature reservoirs. The parameters considered were the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The mannanase enzyme is widely used at the industrial level such as in feed, medicines, and in the upstream oil industry as a gel breaker. Mannanase breaks the β-1,4-glycosidic bonds in guar gum with fewer residues [11]. As compared to others gel breakers, the mannanase enzyme was first isolated from hot spring bacteria to work in extreme oil wells at high temperatures.…”
Section: The Need For Direct Evolution To Increase the Thermostabilit...mentioning
confidence: 99%
See 2 more Smart Citations
“…The mannanase enzyme is widely used at the industrial level such as in feed, medicines, and in the upstream oil industry as a gel breaker. Mannanase breaks the β-1,4-glycosidic bonds in guar gum with fewer residues [11]. As compared to others gel breakers, the mannanase enzyme was first isolated from hot spring bacteria to work in extreme oil wells at high temperatures.…”
Section: The Need For Direct Evolution To Increase the Thermostabilit...mentioning
confidence: 99%
“…Enzyme breakers have several advantages compared to traditional chemical oxidizers such as being environmentally friendly, their ability to break long-chain polymers without altering near-wellbore petrophysical impairment, and their effectiveness-a minimal number of enzymes can do a lot of work because of their catalytic nature, etc. [11]. Conventionally, the enzyme breakers α-1,6-galactosidase and β-1,4-mannanase were isolated from the hyperthermophilic bacterium Thermotoga neapolitana to degrade guar gum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The separation of enantiomers in an analytical and preparative scale is undoubtedly a matter of crucial importance in diverse research areas [ 1 ]. Liquid chromatography (LC) using chiral stationary phases (CSPs) proved to be the most versatile and useful approach for the evaluation of enantiomeric purity in quality control [ 2 , 3 ], the preparative enantioresolution process [ 4 , 5 ], monitoring enantiomeric reactions [ 6 , 7 ], food analysis [ 8 , 9 ], the stereochemistry determination of natural compounds [ 10 , 11 ], pharmacokinetic [ 12 ] and environmental studies [ 13 , 14 ], among other applications. Over the years, several types of CSPs have been developed which comprise polysaccharide derivatives, Pirkle-type, cyclodextrins, crown-ether, proteins, macrocyclic antibiotics, ion-exchange, cyclofructans, synthetic polymers and molecularly imprinted CSPs [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the great importance of enzyme activity in attacking the polymer chains, several studies have been conducted on various enzyme breakers that can degrade the glycosidic bonds of guar-based polymers, such as amylose, cellulose, galactose, pectinose, and mannanose. ,, There are various types of mannanase enzymes, which act on mannanose polymers (the backbone of guar polymer), but only a certain type exhibits higher activity at high temperatures and a wide pH range. , From the comparative studies conducted by Meng et al using mannanase, amylase, cellulase, pectinase, and xylanase, it was reported that only mannanase provides a rapid and homogeneous guar-polymer breakage at low concentrations retaining its activity over a wide range of temperatures and pH ranges. However, it was also found that the activity of wild mannanase strain is limited to 150–160 °F.…”
Section: Introductionmentioning
confidence: 99%